Accounting Paradigms, Models and Practical Applications: Facing Development Challenges - T. Yu. Serebryakova (Учёт. Анализ. Аудит, 2025)
This article explores the evolution of accounting, its scientific foundations, and the impact of historical concepts on its development. It is a thought-provoking piece designed to engage practitioners and spur discussions about the future of accounting in our country. We examine potential paths for accounting’s advancement in the age of automated production and management. Our goal is to categorize different types of accounting, align them with current paradigms, and evaluate the prospects for accounting as a scientific discipline. We employ a systematic approach, logical analysis, legal and linguistic methods, and hypothesis testing. The results offer a classification of existing accounting models and explain their key typological distinctions. We delve into the scientific basis and theoretical principles of accounting. We also critique the regulatory function of our domestic accounting system. In Russia, regulatory documents have blurred the lines between accounting, financial accounting, and related reporting types. Historically, accounting has focused on property protection and profit calculation, defined as the difference between income and expenses over a period. We advocate returning to fundamental accounting and reporting models, including the derivative financial accounting and reporting model. This study will be valuable to researchers and practitioners interested in accounting science and methodology. By developing scientifically grounded approaches to accounting and reporting, we enhance effective management across all levels.